A Degree Based Topological Study of Two Carbon Nanosheets VC5C7 and HC5C7. (9th August 2022) - Ishtiaq, Muhammad; Rauf, Abdul; Rubbab, Qammar; Siddiqui, Muhammad Kamran; Rehman, Ata-ur-; Cancan, Murat
Abstract: Nanomaterials are chemical compounds or substances which are moderately produced and used. Nanomaterials are engineered to reveal novel properties of nanocells that contrast with related non-visible substances, such as expanded consistency, conductivity or synthetic reaction. Topological indexes are quantities related to molecules that capture the harmony of molecular structures and give scientifically related properties, such as: viscosity, boiling point, radius of gravity, and so on. Their demands in genetics, chemistry, physics and nanoscience are infinite. The molecular topology of such compounds would be clarify by the quantitative structure properties relationship (QSPR) and quantitative structure activity relationship (QSAR). Two carbon nanosheet structures such as V C 5 C 7 and H C 5 C 7 have been discussed in this article. We also computed ev-degree and ve-degree based topological indices of these structures.